Solar activity influence on vertical ozone redistribution over Antarctica - Lozitsky, V.V. (Національний антарктичний науковий центр МОН України, 2004)
Study of dynamics of vertical ozone distribution above Antarctic and, for comparison, equatorial zones during complete 11-year's cycle of solar activity was made. Satellite profile ozone data from Nimbus 7 were used. Strong vertical redistribution of an ozone amounts during ozone hole is shown. Correlations analysis between ozone vertical profile data and several solar activity indices was made. An absence of ozone layer response on solar proton events and finding out significant decrease of correlation coefficients at upper stratosphere heights are the main results of the work.